Testing persuasive messages about booster doses of COVID-19 vaccines on intention to vaccinate in Australian adults: A randomised controlled trial. - Maryke S Steffens; Bianca Bullivant; Jessica Kaufman; Catherine King; Margie Danchin; Monsurul Hoq; Mathew D Marques (PLoS ONE, 2023)
Introduction Achieving high COVID-19 vaccine booster coverage is an ongoing global challenge. Health authorities need evidence about effective communication interventions to improve acceptance and uptake. This study aimed to test effects of persuasive messages about COVID-19 vaccine booster doses on intention to vaccinate amongst eligible adults in Australia. Methods In this online randomised controlled trial, adult participants received one of four intervention messages or a control message. The control message provided information about booster dose eligibility. Intervention messages added to the control message, each using a different persuasive strategy, including: emphasising personal health benefits of booster doses, community health benefits, non-health benefits, and personal agency in choosing vaccination. After the intervention, participants answered items about COVID-19 booster vaccine intention and beliefs. Intervention groups were compared to the control using tests of two proportions; differences of ≥5 percentage points were deemed clinically significant. A sub-group analysis was conducted among hesitant participants. Results Of the 487 consenting and randomised participants, 442 (90.8%) completed the experiment and were included in the analysis. Participants viewing messages emphasising non-health benefits had the highest intention compared to those who viewed the control message (percentage point diff: 9.0, 95% CI -0.8, 18.8, p = 0.071). Intention was even higher among hesitant individuals in this intervention group compared to the control group (percentage point diff: 15.6, 95% CI -6.0, 37.3, p = 0.150). Conversely, intention was lower among hesitant individuals who viewed messages emphasising personal agency compared to the control group (percentage point diff: -10.8, 95% CI -33.0, 11.4, p = 0.330), although evidence in support of these findings is weak. Conclusion Health authorities should highlight non-health benefits to encourage COVID-19 vaccine booster uptake but use messages emphasising personal agency with caution. These findings can inform communication message development and strategies to improve COVID-19 vaccine booster uptake. Clinical trial registration: Registered with the Australian New Zealand Clinical Trials Registry (ACTRN12622001404718); trial webpage: https://www.anzctr.org.au/ACTRN12622001404718.aspx.